Magnetic dipole transition rates in B-like and F-like titanium ions measured at a heavy-ion storage ring - Träbert, Elmar; Gwinner, G.; Wolf, Andreas; Tordoir, X.; Calamai, A. G. (Physics letters, 2000)
The rates of the electric-dipole forbidden transitions between the fine structure levels of the ground state in B- and F-like ions of Ti have been measured optically at a heavy-ion storage ring. The lifetime results, (0.627±0.010) ms for Ti17+ and (0.513±0.010) ms for Ti13+, are the most precise for any such transition yet and are in reasonable agreement with theory. An isoelectronic comparison includes data from electron beam and Kingdon-type ion traps.
Available online 10 January 2000
Gesehen am 01.12.2020